Spanish Red Cross' training manuals during the 1918-1919 influenza epidemic - Alberto González García (Universidad de Alicante, 2013)
The target of this article is to analyze the training manuals of practitioners, nurses and Spanish Red Cross nurses to assess how far we can place the introduction of educational content related to public health nursing. The reporting period covers from the configuration of the nursing profession to onset of the first figure with real functions of public health nursing, pediatric nurses. We have selected seven training manuals from the Red Cross, three practitioners training manuals, and five nurses training manuals, published until 1925, to compare the contents of each curriculum. The main conclusions are that the Red Cross stands as one of the protagonists of public health nursing in Spain, due to her performance in times of war and, especially, in times of the influenza epidemic of 1918-1919. Care infectious patients requiring first appeared in the training manuals of the Red Cross nurses following the 1918 influenza epidemic events.